Employee Performance Improvement Through Reward and Work Discipline - Pancasasti, Ranthy (Management Science Research Journal, 2023)
Background – PT. MKN is one of the power cable companies that targets itself to be among the top 3 power cable companies in Indonesia, by increasing the ability of its human resources through Best Recruitment, Placement that is right on target, and evaluates it regularly, not only punishment but also PT. MKN provides Rewards as Feedback for outstanding employees to always improve their performance by making a positive contribution through achieving the targets set by each department after a complete analysis of prioritized work is carried out through measuring the performance of each employee who works for the company. Objectives – The purpose of this study was to analyze the effect of Discipline and Reward on the performance of employees of PT. MKN. Method - This study is to find out about improving employee performance through work discipline and rewards at PT. MKN. The research design used in this research is a quantitative research type. Analysis of the data used is quantitative analysis, with the PLS SEM test method. Novelty – The novelty in this research is that no previous research that discusses the influence of Discipline and Rewards on the performance of employees of PT. MKN. Limitations – The limitation in this research is to analyze the influence of Discipline and Reward on the performance of employees of PT. MKN Results - The results showed that reward and discipline had a positive and significant effect partially and simultaneously on the performance of employees of PT. MKN.